Urban Farming in Polybag: Socialization for Urban Areas: Sosialisasi Urban Farming di Daerah Perkotaan - Nanda Trisna Prihartini; Natasya Fadilah; Muhammad Zakki Fahmi; Md. Aminul Islam Khan; Desti Agustia Putri; Laurent Regina Anjani; Azki Nur Halimah; Gabriella Pusparini Tasya Patriciya Diamonds; Septiana Dina Mahiro; Mubarokah Mubarokah; Gyska Indah Harya (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Urban expansion in Indonesia has led to a significant reduction in productive land, which has impacted household food security and created an economic burden due to fluctuations in horticultural commodity prices. This phenomenon is clearly evident in Asemrowo Village, Surabaya, where high residential density limits the use of backyards as productive spaces. This community service activity aims to enhance residents’ knowledge and technical skills in implementing polybag-based urban farming. The implementation method comprises three main stages: community education through interactive lectures, training through hands-on cultivation of chili peppers (Capsicum frutescens L.) and eggplants (Solanum melongena), and participatory mentoring. Program effectiveness was measured using pre-test and post-test instruments administered to participants. Evaluation results indicated a significant improvement in participants’ competencies; the average conceptual understanding score increased from 30 to 80, while the average technical and application score rose from 25 to 80. The use of polybags proved to have a high level of acceptance due to their flexibility and cost-efficiency for limited land. It was concluded that the integration of theoretical outreach and practical mentoring methods successfully changed residents’ perceptions and provided them with the ability to implement urban agriculture as a strategy for strengthening sustainable community food security